Fostering Well-Being in the Elderly: Translating Theories on Positive Aging to Practical Approaches - Bar-Tur, Liora (Frontiers in Medicine, 2021)
This article overviews positive aging concepts and strategies to enhance well-being in the elderly and then presents a translation of theories on positive aging to practical approaches for Positive Aging. Drawing upon positive psychology and positive aging research and tools, this program is designed to help older adults improve their well-being by acquiring skills and strategies to cope with present and future challenges. The Mental Fitness Program for Positive Aging (MFPPA) can enhance seniors’ quality of life by increasing their vital involvement and active engagement in life. This model is most appropriate for communitydwelling individuals. It can easily be conducted in wide range of adult education programs in community centers, sheltered homes, and primary care clinics. It can also be conducted through online psychoeducational training.